Natural Antioxidants, Health Effects and Bioactive Properties of Wild Allium Species - Petropoulos, Spyridon A.; Di Gioia, Francesco; Polyzos, Nikos; Tzortzakis, Nikos G. (My University, 2020)
BACKGROUND: There is an increasing interest from the pharmaceutical and food industry in natural antioxidant and bioactive compounds derived from plants as substitutes for synthetic compounds. The genus Allium is one of the largest genera, with more than 900 species, including important cultivated and wild species, having beneficial health effects. OBJECTIVE: The present review aims to unravel the chemical composition of wild Allium species and their healthrelated effects, focusing on the main antioxidant compounds. For this purpose, a thorough study of the literature was carried out to compile reports related to health effects and the principal bioactive compounds. Considering the vast number of species, this review is divided into subsections where the most studied species are presented, namely Allium ampeloprasum, A. flavum, A. hookeri, A. jesdianum, A. neapolitanum, A. roseum, A. stipitatum, A. tricoccum, and A. ursinum, with an additional composite section for less studied species. METHODS: The information presented in this review was obtained from worldwide accepted databases such as Scopus, ScienceDirect, PubMed, Google Scholar and Researchgate, using as keywords the respective names of the studied species (both common and Latin names) and the additional terms of"antioxidants" "health effects" and "bioactive properties". CONCLUSION: The genus Allium includes several wild species, many of which are commonly used in traditional and folklore medicine while others are lesser known or are of regional interest. These species can be used as sources of natural bioactive compounds with remarkable health benefits. Several studies have reported these effects and confirmed the mechanisms of action in several cases, although more research is needed in this field. Moreover, considering that most of the studies refer to the results obtained from species collected in the wild under uncontrolled conditions, further research is needed to elucidate the effects of growing conditions on bioactive compounds and to promote the exploitation of this invaluable genetic material.
Keywords: Alliaceae; Health effects; Natural antioxidants; Organosulfur compounds; Saponins; Wild species